Blue light-promoted radical sulfoximido-chalcogenization of aliphatic and aromatic alkenes. Issue 7 (17th March 2021) - Chen, Hongyi; Chen, Li; He, Ze; Zeng, Qingle
Abstract : A transition metal-free synthesis of N -(arylthio/seleno)ethyl sulfoxidmines via blue LED light-promoted radical sulfoximido-chalcogenization of aliphatic and aromatic alkenes was developed. Abstract : A transition metal-free synthesis of N -(arylthio/seleno)ethyl sulfoxidmines via blue light-promoted radical sulfoximido-chalcogenization of aliphatic and aromatic alkenes was developed. The sulfoximidation process demonstrated high chemoselectivity and allowed a broad substrate scope, completing the sulfoximido-chalcogenization of alkenes in good yields.